The Effect of Mini Billiard Games On The Concentration of Autistic Children at The Mitra Ananda Karanganyar Autism Center - Najla Nandika Ghasani; Erma Kumala Sari; Sugini Sugini (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2025)
This research aims to examine the effect of mini billiards games on the concentration of autistic children at the Mitra Ananda Karanganyar Autism Center. This study uses a quantitative research method with a Single Subject Research (SSR) approach that applies an A-B-A design. The subjects of this study are 12-year-old children with autism spectrum disorder at the Mitra Ananda Karanganyar Autism Center. Data collection was conducted using an observation sheet with 10 items that assessed the children's lack of concentration in terms of concentration. The data obtained were analyzed using descriptive statistical techniques with visual data analysis, including analysis within and between conditions. The results of the data analysis showed that subject T had an average duration of non concentration behavior of 393.55 seconds in the baseline-1 phase (A1), 365.27 seconds in the intervention phase (B), and 278.44 seconds in the baseline-2 phase (A2). These data indicate a decrease in non-concentration behavior in subject T after using the mini billiard game intervention. The results of the study show a low percentage of overlap, indicating that the mini billiard game has an effect on the concentration of autistic children at the Mitra Ananda Karanganyar Autism Center.